Democracy promotion a critical introduction - Bridoux, Jeff.; Kurki, Milja (Milton Park, Abingdon, Oxon ; New York : Routledge, 2014)
'This critical introduction to democracy promotion seeks to provide the reader with an understanding of some of the key dynamics and contentions revolving around this controversial policy agenda'--
1. Critical theory and democracy promotion -- 2. Who does democracy promotion and how? -- 3. Is democracy promotion about defence of values or about the safeguarding of interests? -- 4. Is democracy promotion regime change? -- 5. Is democracy promotion context-sensitive? -- 6. Is democracy promotion limited to achieving political reform or does it aim to advance liberal economic reform? -- 7. Is democracy promotion reflective of and constructive of'hegemonic' power relations?.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Democratization; Democracy; Political culture; Electronic books